Diagnosis, Manifestations, Laboratory Investigations, and Prognosis in Pediatric and Adult Cushing’s Disease in a Large Center in China - Zheng, Xueqing; Wang, He; Zhang, Wentai; Feng, Shanshan; Liu, Yifan; Li, Shuo; Bao, Xinjie; Lu, Lin; Zhu, Huijuan; Feng, Ming; Wang, Renzhi (Frontiers in Endocrinology, 2021)
Purpose: Cushing’s disease (CD) is a rare disease that contributes to 70-80% hypercortisolemia, which presents similarities and differences between pediatric and adult patients, and even between male and female patients. However, the comparative study of CD is still insufficient. The aim of the study is to make a systematic comparison to reveal the gender differences in children and adult patients, helping clinicians to provide optimal treatment. Methods: We conducted a retrospective research consisting of 30 pediatric and 392 adult CD patients in a single centre in Peking Union Medical College Hospital. All 422 patients showed symptoms related to hypercortisolism and received adenoma excision surgery between 2014 to 2020. Results: For the accuracy of diagnosis, the sensitivity of BIPSS at baseline in pediatric patients was lower than in adults but increased greatly after desmopressin stimulation. However, the accuracy of lateralization for BIPSS was not preferred for prediction. As for clinical manifestations, growth retardation, weight gain, hirsutism, acne were more prevalent for children, while for adults, hypertension, osteopenia, glucometabolic disorder, easy bruising, hair loss, and weight loss were more frequently seen. As previously reported, we observed a significant difference between the male prevalence of pediatric and adult patients (50% vs. 17%, P < 0.001), which was possibly caused by the more severe and earlier-onset of a series of symptoms. Gender-related comparison showed greater morbidity of nephrolithiasis, hypokalemia, hypertension, easy bruising, osteopenia, and striae for male patients, while irregular menses, hirsutism, and hair loss were more common for female patients. Further analysis showed that the secretory activity of the PA axis was higher for males, contributing to the more severe clinical manifestations. For patients treated with transsphenoidal pituitary surgery (TSS), the immediate prognosis could be predicted by operation history, invasiveness, Ki-67, and information provided by MRI, including tumour size and Knosp grading. However, we still lack methods to predict long-term prognosis. Conclusions: Our study is the first detailed and systematic comparison between pediatric and adult CD patients. Further exploration of the impact of CD on different genders reveals a more severe and probably an earlier-onset pattern of CD for male patients.